Regionalismo en Asia Central: un balance - Duarte, Paulo (El Colegio de México A.C., 2015)
This article seeks to illustrate the main characteristics of re- gionalism in Central Asia. This regionalism, as conceived by the Central Asian republics, has been rather timid, has had little effect, and contributed little to regional integration. For this integration to take place, it is necessary for the Central Asian republics to adopt an attitude of greater cooperation, which means increasing the importance of the existing multilateral organizations in the region. This paper defines “Central Asia” as the five states in the Community of Independent States: Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan.